Analysis of Students' Comprehension in Solving Social Arithmetic Problems Based on Polya Steps - Durratul Jannah Binti Abdullah Haris; Tatang Herman; Aan Hasanah (Green Publisher Indonesia, 2025)
Problem solving ability is one of the abilities that must be possessed by students, to increase logical, creative, and critical thinking in learning mathematics. One way that can be used to solve problems well is to use Polya's problem solving steps. However, not all students are able to solve social arithmetic problems using Polya's problem solving steps appropriately. This research aims to analyze junior high school students' understanding in solving social arithmetic problems based on Polya's steps. The method used in this research is descriptive with a qualitative approach. This research was conducted randomly to 30 junior high school students in grade VIII. This research uses test instruments and interviews with students and will be assessed based on the indicators met. Based on the research conducted, it was obtained that the students' problem understanding indicator was 50%, solution planning was 70%, implementation of the solution plan was 40%, and checking back was 23.33%. So based on the results of this study, students need to improve their ability to solve social arithmetic problems using Polya's steps.